A socioeconomic approach to the profile of microcredit holders from the Hispanic minority in the USA - Salvador Cruz Rambaud; Joaquín López Pascual; Emilio M. Santandreu (Financial Innovation, 2023)
Abstract The subject of this study is the microcredit market in the USA, more specifically in Florida. The justification for choosing this specific state is the massive presence of the Hispanic population. This will facilitate a generalization of the obtained results to the microcredit market in Latin American countries. Thus, the objective of this study is to analyze the profile of microcredit holders and their companies from socioeconomic and financial points of view. As our data also consider the degree of repayment of the microloans included in the sample, the clients’ profile is related to the punctuality or default of their corresponding loan repayments using the methodology of multinomial logit regression. The variables used in this study refer to personal information concerning borrowers (gender, age, education level, and marital status), the economic situation of their respective companies (closeness to the lender, number of workers, and revenues), and the characteristics of granted loans (principal, term, and purpose). However, the results of the regression show that only two variables are significant at the 5% significance level: the borrower’s age, which has a positive effect on repayment punctuality, and the loan term, which exhibits a negative effect. The findings of this study have clear implications, as they can help lenders design suitable microloans adjusted to customer profiles. Finally, future research should include other demographics and characteristics of affected companies.